Representative of Luft and Harry Ingham Theory in the User Interface of Tiktok Application - Siti Hartatik; Fanny Hendro Aryo Putro; Topan Setiawan; Wahyuning Chumaeson (Postgraduate, University of Mataram, 2024)
The shift in the form of communication between individuals through social media is an interesting agreement, technological advances that have occurred at this time have created many new media as a place for self-disclosure and expressing themselves. TikTok social media is one of the most widely used social media, especially among generation Z. Currently TikTok is growing as a lifestyle and phenomenon, but not everyone has the courage toexpress themselves or self-disclosure using social media to become a place for interpersonal communication between TikTok social media users in the form of self-disclosure to others. Supported by a good user interface and able to provide user experience to its users, theTikTok application has a user friendly appearance, where the buttons available have a clear shape and location that is easy to remember. This study examines how the form of self- disclosure or self-disclosure among generation Z on TikTok social media. The method used isa qualitative method. Self disclosure on TikTok social media is in the form of confessions of the heart, feelings, thoughts, emotions and information where informants feel relieved after doing self disclosure on TikTok social media with support from virtual friends as a form of replay. There is trust and a sense of comfort that exists and also knows each other through TikTok social media between himself and friends so that he feels safer when making self- disclosures because he is in the same frequency.